2003
DOI: 10.1176/appi.ajp.160.10.1887
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Brain Dopamine Concentration With Dietary Tyrosine Plus Phenylalanine Depletion: An [11C]Raclopride PET Study

Abstract: This is the first demonstration of an effect of a dietary manipulation on brain dopamine release in humans. This result provides support for the further investigation of the role of dietary manipulations in the treatment of neuropsychiatric disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
89
3
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(103 citation statements)
references
References 5 publications
7
89
3
2
Order By: Relevance
“…Indeed in a recent PET imaging of TYR depletion, we found that the increase in D 2 receptor binding as measured by [ 11 C]raclopride correlated significantly with the fall in the plasma ratio of TYR and PHE to large neutral amino acids (Montgomery et al, 2003). A similar finding was reported by Leyton et al (2004) who found that the ability of TYR depletion to attenuate the decrease in [ 11 C]raclopride binding produced by d-amphetamine correlated linearly with reduction in plasma TYR levels.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Indeed in a recent PET imaging of TYR depletion, we found that the increase in D 2 receptor binding as measured by [ 11 C]raclopride correlated significantly with the fall in the plasma ratio of TYR and PHE to large neutral amino acids (Montgomery et al, 2003). A similar finding was reported by Leyton et al (2004) who found that the ability of TYR depletion to attenuate the decrease in [ 11 C]raclopride binding produced by d-amphetamine correlated linearly with reduction in plasma TYR levels.…”
Section: Discussionsupporting
confidence: 87%
“…Although administration of the BAL mixture increases plasma levels of PHE and TYR, (Sheehan et al, 1996) overall, as found in the present study, it produces some lowering in the plasma ratio of TYR þ PHE : BCAA Montgomery et al, 2003). For reasons that are not clear, the extent of this reduction varies somewhat between studies but it is always substantially less than that produced by the TYR-free mixture.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Using this method, serotonin depletion was found to decrease PPI in healthy humans (Phillips et al, 2000a). On the other hand, acute tyrosine/phenylalanine depletion (ATPD) has been shown to selectively decrease dopamine synthesis and release (Jaskiw and Bongiovanni, 2004;Leyton et al, 2000;McTavish et al, 1999aMcTavish et al, , b, 2001aMehta et al, 2005;Montgomery et al, 2003), and impair dopamine-dependent cognitive processes such as working memory (Harmer et al, 2001;Harrison et al, 2004). The effects of dopamine depletion via ATPD on PPI and P50 suppression are yet to be determined.…”
Section: Introductionmentioning
confidence: 99%